CURRENT STATE AND PECULIARITIES OF DEVELOPMENT OF MARKETING INNOVATIONS AT ENTERPRISES (INNOVATIVE ECONOMY, 2020)
Marchyshyn N.Ya., Hrynchutskyi V.I. CURRENT STATE AND PECULIARITIES OF DEVELOPMENT OF MARKETING INNOVATIONS AT ENTERPRISESPurpose. The aim of the article is to research the dynamics of development of marketing innovations and their variants in the modern period, to distinguish its main regularities and outline the main opportunities and prospects of development of marketing communications of enterprises on an innovative basis.Methodology of research. The methodological basis of the study was the theoretical development of domestic and foreign scientists on the development of innovative marketing technologies and ways of their implementation. To achieve the goal, a dialectical method and a systematic approach to the study of the essential characteristics and features of sensory (neuromarketing), guerrilla, lateral and holistic marketing are used, and the monographic, abstract and logical methods are also used in the research process.Findings. The basic directions of innovative development of marketing communications are determined. The practical advantages of adaptation of components in the realities of economic activity of domestic enterprises are revealed. The practical feasibility of using the method of lateral marketing for the domestic market at this stage of its development is substantiated.Originality. The practical advantages, expediency and possibilities of using lateral marketing approaches for leading milk processing enterprises are substantiated.Practical value. Possible practical implementation of the results of this study is the search for ways to combine individual elements of indicative influence with other innovative marketing strategies for building a dynamic integrated innovation marketing system, as well as the adaptation of certain innovative marketing tools to the practice of domestic enterprises, as discussed in the article.Key words: innovative marketing; sensory marketing; neuromarketing; guerrilla marketing; lateral marketing; holistic marketing; consumer choice; neurobiological indicators.
Keywords: Key words; innovative marketing; sensory marketing; neuromarketing; guerrilla marketing; lateral marketing; holistic marketing; consumer choice; neurobiological indicators.